(untitled) (Research, Society and Development, 2026)
This article aims to analyze, in light of classical and contemporary theoretical references, the contributions of jumps and jumps to sensory learning in Early Childhood Education, understanding play as a structuring principle of pedagogical practice in early childhood. Part-is the assumption that child development occurs in an integrated way, articulating sensory, corporeal, cognitive, affective and social dimensions, sendo o brincar a principal linguagem por meio da qual a criança interage com o mundo e constrói meanings. The study is based on the contributions of Piaget, Vygotsky, Wallon and Kishimoto, as well as Andrade’s reflections on teacher training and pedagogical intentionality in the use of play. Methodologically, it is a qualitative research, of a bibliographic and analytical-reflexive nature, built from the conceptual discussion on sensory learning, pedagogical media and teacher training, supported by official documents such as the National Curricular Base. The results indicate that leaps and bounds, when planned with intentionality and articulated to curricular objectives, broaden sensory experiences, strengthen bonds, promote autonomy and potentialize integral development. It is concluded that play is a structuring element of Early Childhood Education and that its effectiveness as a qualified pedagogical practice depends on continuous, critical and theoretically based teaching training.